The Effectiveness of Slimber Ice Against Thirst Intensity In Hemodialysis Patients With Chronic Kidney Disease - Jenita Laurensia Saranga; Serlina Sandi; Wirmando Wirmando; Yuliana Tola'ba; Sandy Setiawan Ghae; Cantika Wulandari; Anita Panjaya (Universitas Muhammadiyah Semarang, 2023)
Chronic Kidney Disease (CKD) is a progressive & irreversible impairment of kidney function. The replacement therapy in CKD that is widely chosen is hemodialysis. CKD patients undergoing hemodialysis should limit fluid intake during dialysis so that excess fluid does not occur, but the result of fluid restriction will trigger the onset of thirst so patients are less likely to adhere to the fluid intake diet. Slimber ice is an intervention of choice in the management of thirst. This study aims to analyze the effect slimber-ice against thirst intensity in hemodialysis patients with CKD at Stella Maris Hospital Makassar. The type of research used is Pre-Experimental with One Group Pre-Post Test Design. Sampling using the Non-Probability Sampling method with the Consecutive Sampling technique with a total sample of 40 respondents. This study provided intervention in hemodialysis patients with CKD in the form of slimber-ice. The implementation of the intervention begins with a Pre-Test (measurement of thirst intensity) using the Visual Analogue Scale (VAS) instrument, then giving slimber-ice for 5 weeks (2x a week) then a Post-Test is carried out. The results of the study described the majority of respondents aged 56-65 years, namely 15 respondents (37,5%), male gender 29 respondents (72,5%), high school last education 28 respondents (70%), & employment status was not working 22 respondents (55%), then the intensity of thirst before the intervention of the majority of moderate thirst was 29 respondents (72,5%) & after the majority of mild thirst 33 respondents (82,5%). Wilcoxon test analysis was obtained p = 0.000 ˂ α = 0.05 so that there was a significant effect slimber-ice agains thirst intensity in hemodialysis patients with CKD. Researchers recommend slimber-ice as one of the self-interventions in restraining thirst to prevent an imbalance of body fluids due to overhydration.